Development and Impact Monitoring of a Communication Strategy for the CGIAR Climate Security Program - McLaughlin, Isabel; McKeown, Peter; Spillane, Charles; Läderach, Peter R.D. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The purpose of this research paper is to investigate the different aspects of a communications strategy to determine its success for future use and to identify any adaptations and adjustments necessary for improvement. It is vital that research endeavours have the appropriate tools to convey messages of scientific significance to both policy makers and the public for the findings to be of value. This paper analyses the data from a communication strategy formulated for CGIAR Climate Security, a new initiative by CGIAR intended to highlight the extensive pathways in which outcomes of climate change may exacerbate conflict in vulnerable regions. The communications strategy focuses on four main aspects – a Climate Security website, Climate Security webinars streamed from Whova, YouTube and through the UN Global Dispatch Podcast, blog posts and a social media campaign spread across three platforms, Twitter, Facebook and LinkedIn. The strategy was developed and executed over a two month period, where results from Twitter Analytics and Google Analytics were analysed along with the engagement generated from all other platforms. Analysis of Twitter Analytics was focused on aspects of tweets which drove URL clicks and visitors to the Climate Security website. The most effective tweets for generating URL clicks were most commonly accompanied by a video, posted later in the day (afternoon and evening) and later in the week (Thursday to Sunday). The data from Google Analytics suggest that high levels of activity on the Climate Security website produced levels of high engagement. When events such as the Climate Security webinars were scheduled and promoted through social media a pattern of high engagement was observed compared to times of low activity and promotion. It can be argued that the communications strategy was a success with the Climate Security website generating 62,894 visits from 2,294 different users over the two-month period. Twitter posts generated a total of 152,796 impressions on users. The Climate Security webinars had a combined audience of 16,496 views across all streaming platforms. For sustainable impact monitoring it would be necessary to conduct similar follow-on studies in the future to analyse the impact of changes made to the communication strategy developed for the CGIAR Climate Security.